CORRELATION OF CHEMOTHERAPY CYCLES WITH STAGE OF DEPRESSION IN BREAST CANCER PATIENTS - Rahayu, Mulyati Sri; Nadira, Cut Sidrah (E-Jurnal Medika Udayana; Vol 13 No 9 (2024): E-Jurnal Medika UdayanaDO - 10.24843/MU.2024.V13.i09.P10, 2024)
Breast cancer is the most common cancer in women around the world, including Indonesia. Women with breast cancer are more vulnerable to psychological symptoms compared to the general population before or after treatment. Psycological symptoms such as depression, anxiety, and fatigue correlate with increasing pro-inflammatory mediators as the response to the malignancy process and also anti-cancer treatment. The psychological symptoms have a bad impact on cognitive functions and lower the quality of life of cancer patients. The research aims to determine the depression prevalence and chemotherapy cycle correlation with the severity of depression in breast cancer patients at Rumah Sakit Umum Cut Meutia, Aceh Utara Regency. This study is an analytical observational study with a cross-sectional approach. The study sample of 66 breast cancer patients undergoing chemotherapy at the Rumah Sakit Umum Cut Meutia, Aceh Utara was obtained using the consecutive sampling method in accordance with the established inclusion and exclusion criteria. The chemotherapy cycle is known from medical records and depression score assessments referring to the Depression Anxiety Stress Scales questionnaire (DASS 42). The correlation of chemotherapy cycles with depression scores was analyzed using the Spearman correlation test. The results showed that the characteristics of the sample were mostly aged 46–55 years, already in stage IV, undergoing cycle 2 or 3 chemotherapy, using an antracylin-based regimen, and not yet depressed (normal). Correlation analysis showed a positive correlation (p 0.001) of moderate degree (r = 0.42) between chemotherapy cycles and degrees of depression. It can be concluded that increasing chemotherapy cycles tends to increase the severity of depression.